67‐1: Comparison of In‐folding and Out‐folding Stress on Electrical Performance of Poly‐Si TFTs on Polyimide Substrate for Foldable AMOLED Display. Issue 1 (28th June 2022) - Billah, Mohammad Masum; Siddik, Abu Bakar; Kim, Dongjin; Lee, Suhui; Cho, Young Jo; Rabbi, Md Hasnat; Jang, Jin
Abstract : A comparison between cyclic out‐folding and in‐folding strain on flexible poly‐Si TFTs for foldable AMOLED display is reported. TFT under out‐folding stress exhibits severe degradation including positive threshold voltage (VTh ) shift with unstable drain current (ID) than in‐folding, which is related to defect‐generation at poly‐Si grain‐boundary and justified using TCAD simulation. Stable low leakage current (<1 pA) after 30, 000 mechanical folding cycles confirms the defect formation within poly‐Si and grain boundary protrusions. Electrical performance recovery using vacuum annealing after folding stress verifies the origin of electrical degradation as metastable traps generation.